A Skills beyond School Review of the Slovak Republic - Fazekas, Mihály (OECD Publishing, 2016)
Higher level vocational education and training (VET) programmes are facing rapid change and intensifying challenges. What type of training is needed to meet the needs of changing economies? How should the programmes be funded?  How should they be linked to academic and university programmes?  How can employers and unions be engaged? The country reports in this series look at these and other questions. They form part of Skills beyond School, the OECD policy review of postsecondary vocational education and training
Keywords: Education; Slovak Republic